The Effectiveness of Using an Interactive e-Module to Improve Learning Outcomes - Darpiyah, Darpiyah -; Sulastri, Sulastri - (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
This research aims to determine the effectiveness of using an interactive e-module based on a website using Google Site for tax-related material. This research phase employs a two-group pretest-posttest with control group research design. The research subjects are 50 students from the 11th-grade Accounting class at SMKN 1 Prigen. Data collection is carried out using a test technique in both the experimental and control groups. The data analysis technique involves qualitative data. In the experimental group, an improvement in learning outcomes of 0.7006 was obtained, indicating that the interactive electronic tax-based website module is categorized as highly effective in enhancing learning outcomes. The results of the T-test calculation for learning outcomes reveal that the interactive electronic tax-based website module has a significant and effective impact on improving learning outcomes.